2015
DOI: 10.5897/ajmr2015.7389
|View full text |Cite
|
Sign up to set email alerts
|

Mycobiota from the eggs, nests and stillbirths of Eretmochelys imbricata Linneus 1766 (Testudines: Cheloniidae) in Pernambuco State, Brazil

Abstract: Eretmochelys imbricata Linneus 1766 was the subject of trade due to egg collection and consumption of the flesh of the females, being the fishery one of the main impacts towards the coastal area. The pathogens are also worrying factors of mortality of sea turtles especially those caused by fungi; these can cause the death of embryos and cutaneous mycoses. This study aimed to investigate the mycoflora isolated from soil, eggshells and stillbirths from E. imbricata in three beaches of Ipojuca (Brazil). We record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Fungi from the Fusarium genus are considered saprophytes, but they can act as opportunistic pathogens in immunocompromised subjects or in developing embryos, especially under environmental stress conditions (Güçlü et al, 2010). Critically, the two Fusarium species identified in this study, F. solani and F. oxysporum, are recognised as causes of reduced hatching rates in sea turtle nests, and can occasionally cause 100% mortality in turtle embryos (Güçlü et al, 2010;Keene et al, 2014;Neves et al, 2015;Sarmiento-Ramírez et al, 2010). The ability of F. solani and F. oxysporum to penetrate egg shells and invade the embryonic tissue is due to the production of lipolytic and proteolytic enzymes that degrade inorganic and organic egg components (Phillott, 2004).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Fungi from the Fusarium genus are considered saprophytes, but they can act as opportunistic pathogens in immunocompromised subjects or in developing embryos, especially under environmental stress conditions (Güçlü et al, 2010). Critically, the two Fusarium species identified in this study, F. solani and F. oxysporum, are recognised as causes of reduced hatching rates in sea turtle nests, and can occasionally cause 100% mortality in turtle embryos (Güçlü et al, 2010;Keene et al, 2014;Neves et al, 2015;Sarmiento-Ramírez et al, 2010). The ability of F. solani and F. oxysporum to penetrate egg shells and invade the embryonic tissue is due to the production of lipolytic and proteolytic enzymes that degrade inorganic and organic egg components (Phillott, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…developing embryo conditions. In particular, Fusarium solani and Fusarium oxysporum have been reported in the nests of different turtle species in Turkey, Costa Rica, Australia, Brazil, Cape Verde and Italy (Güçlü et al, 2010;Keene et al, 2014;Neves et al, 2015;Phillott and Parmenter, 2014). Fusarium falciforme and Fusarium keratoplasticum have also been reported in loggerhead sea turtle nests in the USA (Bailey et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies also suggested that the observed increase in hatching success in nests below the high tide line may be due to natural tidal washing, which could remove microbes that are intolerant to saltwater. In contrast, bacterial richness and diversity may increase in the low, middle, and high zones of beach with increasing nest density, probably due to the less stable osmotic environment caused by the tides (Neves et al 2015;Hoh et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several bacterial species have even been shown up to 100% nest mortality (Booth and Dustan 2018). Several studies have suggested that sea turtle embryo mortality is associated with the high microbial load resulting from the decomposition of contaminated eggs during subsequent nesting events (Neves et al 2015;Hoh et al 2019;Gleason et al 2020). In addition, nutrient loads and bacterial abundance in the sand at sea turtle nesting beaches are much higher than non-nesting beaches (Peay et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…FSSC was found to be widely distributed, and many studies have isolated FSSC from sea turtle eggs in nesting sites around the world (e.g., Bailey et al, 2018;Neves et al, 2015;Phillott, 2004;Sarmiento-Ramírez et al, 2014). Sarmiento-Ramírez et al (2010) implied that FSSC poses an extremely high risk to the survival of sea turtles, following large numbers of failed loggerhead turtle eggs found having symptoms of fungal infection by FSSC.…”
Section: Introductionmentioning
confidence: 99%